PELATIHAN PEMANFAATAN APLIKASI ONLINE UNTUK BAHAN EVALUASI BELAJAR SISWA PADA MTS NEGERI BATU MERAH AMBON - Palembang, C. F.; Radjabaycolle, Jefri E. T. (Jurusan Matematika FMIPA Universitas Pattimura, 2023)
In 2020 Indonesia was hit by the Covid-19 pandemic which also occurred in various countries so that it had an impact on the world of education. Teaching and learning activities that were previously accustomed to face-to-face learning have changed to online or online learning. Every level of education must be able to adapt to the online learning model, so good cooperation between teachers, parents and students is needed. For the education level of Junior High School or State Madrasah Tsanawiyah (MTsN) Ambon, parents must spend more time than usual accompanying student learning so that they can assist teachers in controlling children. Conversely, teachers are required to be able to provide material as interesting as possible so that students are not bored in the teaching and learning process and the learning evaluation process can run well. The UNPATTI Computer Science Study Program took the initiative to conduct training on the use of online applications for student learning evaluation materials in the city of Ambon addressing the dynamics of online learning for MTsN level students. This activity uses a website-based application that can be used to create learning media such as quizzes, tests, and evaluation of student scores